Potential therapeutic applications of infusions and hydroalcoholic extracts of Romanian glutinous sage (Salvia glutinosa L.) - Nicolescu, Alexandru; Babotă, Mihai; Ilea, Maria; Dias, Maria Inês; Calhelha, Ricardo C.; Gavrilaș, Laura; Rocchetti, Gabriele; Crișan, Gianina; Mocan, Andrei; Barros, Lillian; Pârvu, Alina Elena (Frontiers in Pharmacology, 2022)
Ethnopharmacological relevance:Salvia glutinosa, also known as the glutinous sage, has been used in Romanian folk medicine in the treatment of inflammation, injuries, and mild infections. However, there is no direct scientific evidence to demonstrate these activities. Aim of the Study: The present research was based on evaluating antioxidant, antiproliferative, and α-glucosidase inhibitory activity of S. glutinosa extracts, as well as the in vivo anti-inflammatory activity. Materials and Methods: Infusions and 70% (v:v) ethanol solution extracts of S. glutinosa stems and leaves, collected from two different locations in Romania, were prepared. Ten phenolic compounds were identified and quantified using the LC-DAD-ESI/MSn method, and total phenolic and flavonoid content, as well as in vitro antioxidant (DPPH, ABTS, and FRAP assays), antiproliferative, anti-inflammatory and alpha-glucosidase inhibitory activities were determined. A rat model of induced inflammation with turpentine oil was used for the examination of in vivo effects of the extracts, using diclofenac as an anti-inflammatory control. Results: The highest inhibitory α-glucosidase activity was determined to be IC50 = 0.546 mg/ml for the hydroalcoholic extract made with plant material collected on the road to Sighișoara. The highest cytotoxic activity against HepG2 cell line was determined to be GI50 = 131.68 ± 5.03 μg/ml, for the hydroalcoholic extract made with plant material from Sighișoara. In vivo administration of extract (200 mg lyophilized powder/ml) showed a significant reduction of NO production. Conclusion: Our findings indicate that S. glutinosa extracts exhibit antioxidant, α-glucosidase inhibitory activity, as well as a modest cytotoxic effect on HepG2 cell line. By in vivo administration, the extracts show anti-inflammatory and antioxidant activity, which correlates with the traditional use of the species. The environmental conditions seemed to induce important changes in the chemical composition and the bioactivity of the herbal preparations derived from S. glutinosa.